The Lima Stock Exchange, 1980-1990: an analysis of liquidity, profitability and risk - Wong, David (Universidad del Pacífico, 1991)
This article analyzes Lima's Stock Exchange through 33 securities in the 1980-1990 periods, using the Capital Asset Pricing model. It arrives to the following conclusions: a few securities were liquid assets; not always stock exchange was an attractive alternative; the dollar was one of the best securities; and, all efficient portfolios included low risk deposits, even if these offered a negative real return.